Tvorčestvo M. Ju. Lermontova: motivy, temy, perevody - Marina Bajić; Kaloh Vid, Natalia (2015)
Creativity of M. Yu. Lermontov: Motives, Themes, Translations. New scientific monograph Creativity of M. Ju. Lermonotova, which contains contributions from Russian, Slovenian, Croatian, Serbian and Czech scholars, sheds light on the role and importance of creativity of the great Russian poet, writer and playwright M. J. Lermontov in contemporary Russian and European space. The discussions presented in the monograph clearly illustrate the great interest in this famous Russian romanticist, who in his very short life has enriched both Russian and European cultural treasures with a stunning number of poems, prose and dramatic works. The emergence of this monograph in the European space is of particular symbolic importance, since Lermont's literary oeuvre is closely connected not only with Russian but also with European discourse, especially with Western European romantics, through translations, allusions, references and the establishment of similar thematic nodes. Discussions in the monograph raise many questions about the tradition of translating Lermontov into European languages ​​and bring new insights into the importance of updating translations, the under-researched dimensions of writer prose and dramatics, such as border spaces and analysis from the perspective of Orthodox axiology, and the involvement of Lermontov in the wider Russian literary world. field, new aspects of comparing his biography with the poetic characteristics of creation and the contact of his literary creativity with other forms of art. In all of these areas, the monograph brings new and interesting literary results. The monograph is an interesting read not only for literary researchers, but also for t. i. "Non-sanctified" - other educators who want to get to know Lermont's work better because it still raises more questions than it offers. They will be attracted by interesting data on Lermont's translation into contemporary European languages, reflections on the tragic fate of the great poet, which is also reflected in his works, and a connection to the world of art, films and non-fiction genres, which certainly enriches the monograph as its interdisciplinary character it expands and becomes receptive to lay readers as well.